The Semantic Classification of Phraseological Units with Proper Nouns in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study of phraseological units containing proper nouns in English and Uzbek languages is of particular importance in understanding the interaction between language, culture, and national identity. Phraseological units, as stable word combinations, not only enrich the vocabulary of a language but also reflect the history, traditions, and worldview of a people. The presence of proper nouns within these units gives them a unique semantic and cultural value, since they often embody historical figures, geographical names, literary characters, and other culturally significant elements. This research is devoted to the semantic classification of such phraseological units, with the aim of identifying their common features, differences, and functional roles in both languages. The article explores how proper nouns, when included in phraseological expressions, undergo semantic transformation and acquire figurative meanings that often go beyond their original referential function. For instance, in English, units like “Uncle Sam” or “Achilles’ heel” not only denote specific figures but also express broader notions of the United States or human vulnerability. Similarly, in Uzbek, phraseological expressions such as “Tohir-Zuhra” or “Rustamday bahodir” symbolize love, heroism, and courage, thereby transmitting important cultural concepts. The study analyzes how such units are grouped semantically into categories, including phraseological units denoting human qualities, social relations, moral values, geographical and historical references, and mythological or literary associations. A comparative approach is employed to highlight similarities and differences in the formation and use of these phraseological units in English and Uzbek. The findings show that while both languages use proper nouns to create vivid imagery and cultural connotations, the choice of proper nouns reflects the unique historical and cultural experiences of each nation. English phraseological units are often shaped by Greco-Roman mythology, Biblical traditions, and Western historical figures, whereas Uzbek units are largely influenced by Eastern mythology, folklore, classical literature, and national heroes. The research emphasizes the importance of semantic classification for practical applications in linguistics, lexicography, and language teaching. Understanding these units not only aids in accurate translation and intercultural communication but also enriches the learner’s perception of cultural heritage embedded in language. Moreover, the study underlines the role of proper noun-based phraseological units in shaping national identity and collective memory through language. In conclusion, the semantic classification of phraseological units with proper nouns in English and Uzbek provides valuable insights into the cultural-linguistic worldview of both nations. It demonstrates that phraseology is not only a linguistic phenomenon but also a cultural code that preserves historical experiences and moral values. This analysis contributes to the broader field of comparative linguistics and helps to strengthen cross-cultural understanding through the study of language.